Encapsulation and in vitro release of erythromycin using biopolymer micelle - Huang, Y; Sun, Y; Wang, Q (Cellular and Molecular Biology, 2015)
An amphiphilic block copolymer poly(ethylene glycol)-block-poly[2-(2-methoxyethoxy)ethyl methacrylate] (PEG-b-PMEO2MA) was prepared and the polymer micelle was applied to encapsulate erythromycin. The Critical Micelle Concentration (CMC) of PEG-b-PMEO2MA was determined by the fluorescent probe pyrene. The effects of addition of erythromycin on encapsulation efficiency and drug loading content were investigated. Drug release was also studied in a phosphate buffer solution with a pH of 7.5. The CMC of PEG-b-PMEO2MA is 0.065 mg/mL when the monomer ratio of the hydrophobic block PMEO2MA to the hydrophilic block PEG is equal to 6:4. The encapsulation efficiency and drug loading were 87.1% and 16.8%, respectively, as the loading content of erythromycin in polymeric micelle is equal to 28%. After erythromycin is loaded into the micelle, the size of PEG-b-PMEO2MA micelle becomes approximately thrice the size of unloaded micelle. The loading micelles stably release erythromycin within 180 hours in phosphate buffer, suggesting that the micelle loaded with erythromycin have a good sustained-release effect.